Reproductive Performance of Water Buffalo Cows: A Review of Affecting Factors - Nava-Trujillo, Hector; Valeris-Chacin, Robert; Morgado-Osorio, Adriana; Zambrano-Salas, Simón; Tovar-Breto, Luis; Quintero-Moreno, Armando (Journal of Buffalo Science, 2020)
This article aims to review both the economic impact of reproductive failures on the profitability of water buffalo systems and the effect of different factors on the reproductive performance of water buffaloes. Besides, an overview of various non-hormonal alternatives to improve reproductive performance is made. The optimal reproductive efficiency in water buffaloes implies calving to conception interval around 90 days to reach a calving interval of 400 days, with longer calving intervals having a negative impact on profitability. Reproductive efficiency is the consequence of the interaction of genetic and non-genetic factors, and the recognition of these factors by analyzing the reproductive information must be a priority. Although each factor's impact can be of greater or lesser magnitude depending on the conditions of each herd, some factors like nutrition, milk yield, body condition score, negative energy balance, parity, bull presence, low estrus intensity, and season can be considered high-impact factors. Not all factors are common among farms; therefore each farm must implement a program for the identification, control, and prevention of reproductive problems, especially during early lactation, to prevent a long anestrus; and when artificial insemination is used, so that it is done at the correct time with respect to the beginning of estrus to enhance fertility.